2014
DOI: 10.1021/nn405754d
|View full text |Cite
|
Sign up to set email alerts
|

Fast Synthesis of High-Performance Graphene Films by Hydrogen-Free Rapid Thermal Chemical Vapor Deposition

Abstract: The practical use of graphene in consumer electronics has not been demonstrated since the size, uniformity, and reliability problems are yet to be solved to satisfy industrial standards. Here we report mass-produced graphene films synthesized by hydrogen-free rapid thermal chemical vapor deposition (RT-CVD), roll-to-roll etching, and transfer methods, which enabled faster and larger production of homogeneous graphene films over 400 × 300 mm(2) area with a sheet resistance of 249 ± 17 Ω/sq without additional do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
160
4
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(171 citation statements)
references
References 29 publications
4
160
4
3
Order By: Relevance
“…In addition, GBs with larger grain size exhibit relatively better conductive performance [247,251]. On the other hand, a few experiments [209,252,253] observed that the configuration of GBs or the variation of grain sizes had little effects on the conductive properties of graphene. Recent study [254] also suggested that increasing grain size would be an inefficient way to improve the electrical conductivity of graphene when the grain size is larger than 1 μm.…”
Section: Disorders In Graphene Structurementioning
confidence: 99%
“…In addition, GBs with larger grain size exhibit relatively better conductive performance [247,251]. On the other hand, a few experiments [209,252,253] observed that the configuration of GBs or the variation of grain sizes had little effects on the conductive properties of graphene. Recent study [254] also suggested that increasing grain size would be an inefficient way to improve the electrical conductivity of graphene when the grain size is larger than 1 μm.…”
Section: Disorders In Graphene Structurementioning
confidence: 99%
“…Taking into account these characteristics, many practical applications of graphene have been proposed. The most promising are graphene-based touch screens, which will potentially replace indium-tin-oxide (ITO-) based screens in the future [4,5], batteries and supercapacitors [6][7][8], and composite materials [9,10]. Above that, a single atom thick graphene layer can effectively protect the underlying material against oxidation and/or corrosion [11,12].…”
mentioning
confidence: 99%
“…Complicated tactile sensing system under bland skin is illustrated in Figure 15 . At present, pressure sensors are primarily based on the strength induced variation in capacitance,149, 150 piezoelectricity,151, 152 resistivity,17 triboelectricity 153. And graphene has been applied in the design of light and wearable pressure sensors.…”
Section: The Human‐like Senses and Feedbacksmentioning
confidence: 99%
“…Moreover, the capacitor structure has been measured to exhibit high response sensitivity with fast touch rates. Cho et al developed a rapid thermal chemical vapor deposition (RT‐CVD) for the growth of graphene films and applied to capacitive multi‐touch devices which fixed in the mobile phone ( Figure   16 a) 150. Such graphene films possessed over 400 × 300 mm 2 area with a sheet resistance of 249 ± 17 Ω sq –1 .…”
Section: The Human‐like Senses and Feedbacksmentioning
confidence: 99%
See 1 more Smart Citation